Studies on the chemical composition and biological activities of essential oils of boesenbergia spp. - Zainah, Adam (Universiti Malaysia Sarawak, UNIMAS, 2008)
Essential oils from six of Boesenbergia spp. were studied for their chemical composition and their biological activity. Essential oils were extracted by ydrodistillation and analyzed using gas chromatography/flame ionization detector (GC/FID). The percentage of essential oil obtained from the six species of Boesenbergia ranged from 0.17%to 1.50% with the highest percentage was obtained from the rhizome of Boesenbergia gracilipes, while the B.pulchella gaves the lowest yield. The major chemical compound in B. parva was methylisohexenyl ketone (30.87%) from the leaves oil; α-copaene (13.56%) from the stem oil; methionol (34.21%) from the rhizome oil and epoxy-2-undecenal (15.43%) from the fruit oils. The most abundant compound found in B. pulchella was isogeraniol (80.00%) from the leaves oil; δ-cadinol (16.00%) from the stem oil and eudesmol (44.62%) from the rhizome oil. B. gracilipes was rich with camphor (24.77%) in the leaves oil; perilla aldehyde (22.19%) in the stem oil and lauryl alcohol (14.82%) in the rhizome oils. While1,8-cineole is the most abundant compounds in the leaves (50.56%) , stem (24.39%) and rhizome (33.19%) of B. burttiana. B. grandis was rich in propionylpyrrole (9.18%) from the leaves oil; cedrenol (19.58%) in the stem oil; cinnamic acid (15.73%) in the rhizome and β-elemene (43.43%) in the fruit oil. The major compound in Boesenbergia sp. was methyl laurate (24.88%) from leaves oil; cedrenol (19.58%) in the stem oil and 1,8-cineole (11.06%), in the rhizome oil. Toxicity test of the essential oil of Boesenbergia spp. against brine shrimp, Artemia salina shows that the essential oils from B. parva, B. pulchella, B. gracilipes and B. grandis showed strong toxicity with LC50 ranged from 6.30 μg/mL to 79.43 μg/mL. The most active essential oils in this study were found to be the ones from the leaves of B. parva. The essential oils from B. burttiana and Boesenbergia species showed the less toxicity with the concentration more than 100 μg/mL. Termicidal activity against Nasutitermes sp. showed that all the essential oil studied gave LC50 in ranged of 0.10%-8.00%, except for the fruit oil of B. grandis with LC50 more than 10%. The rhizome oils of B.burttiana exhibited the strongest activity with the LC50 value of 0.10%.